2000
DOI: 10.1021/jp001807g
|View full text |Cite
|
Sign up to set email alerts
|

Excited-State Double Proton Transfer in 3-Formyl-7-azaindole:  Role of the nπ* State in Proton-Transfer Dynamics

Abstract: 3-Formyl-7-azaindole (3FAI) and its derivatives have been synthesized to study the role of the nπ* state in the excited-state double proton transfer (ESDPT) reaction. In 3FAI monomer as well as its associated hydrogenbonded complexes the lowest excited singlet state has been concluded to be in the 1 nπ* configuration. The association constants incorporating the hydrogen bonding formation were determined to be 1.9 × 10 4 (313 K), 2.2 × 10 4 (298 K) and 1.8 × 10 5 M -1 (298 K) for 3FAI dimer, 3FAI/azacyclohexano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
28
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 47 publications
2
28
0
Order By: Relevance
“…People have revealed that the excited states of hydrogen bonds can affect photoinduced electron transfer, ultrafast internal conversion, proton transfer, twisted intramolecular charge transfer, and so on. [16][17][18][19][20][21][22] A specific interest is the PT process through the channels of hydrogen bonded wires, because a variety of transmembrane proteins use and control the proton gradient across biological membranes. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] The photoinduced proton and hydrogen atom transfer (PT/HT) processes are the main reactions associated with hydrogen bonded wires, and the transferring of the proton is usually accompanied by the charge transfer.…”
Section: Introductionmentioning
confidence: 99%
“…People have revealed that the excited states of hydrogen bonds can affect photoinduced electron transfer, ultrafast internal conversion, proton transfer, twisted intramolecular charge transfer, and so on. [16][17][18][19][20][21][22] A specific interest is the PT process through the channels of hydrogen bonded wires, because a variety of transmembrane proteins use and control the proton gradient across biological membranes. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] The photoinduced proton and hydrogen atom transfer (PT/HT) processes are the main reactions associated with hydrogen bonded wires, and the transferring of the proton is usually accompanied by the charge transfer.…”
Section: Introductionmentioning
confidence: 99%
“…ESIPT is a photo‐induced process, in which a proton jumps from a proton donor group to a proton acceptor along with the intramolecular hydrogen bond, which was described first by Waller . In recent years, an increasing attention have been forced on ESIPT reaction because of its wide applications to such systems as laser dyes, molecular switches fluorescence sensors, UV‐light polymer stabilizers, and particularly in biological systems . In fact, there are a number of questions in ESIPT mechanism cannot be answered accurately based on experimental means.…”
Section: Introductionmentioning
confidence: 99%
“…Commonly, the enol-imine form is the most stable form at the room temperature compared with the keto-amine one. [11][12][13][14][15] Photo-induced enol-keto tautomerization (ESIPT) reaction is common in our life and has been extensively investigated. [16][17][18][19][20] The mechanism and dynamics of the ESIPT process for enol-keto conversion has been investigated well in ortho-hydroxy Schiff base molecules in solid, solutions, and in the gas phase under isolated condition.…”
Section: Introductionmentioning
confidence: 99%